Greenland's state-building in a changing Arctic: climate, energy and geopolitics. - Degeorges, Damien (Arctic Portal, 2011)
Young researcher Damien Degeorges, Paris Descartes University, France, talks here in the NRF 6th open assembly in Hveragerði, Iceland, in September of 2011. Please click on the link above to see the video.